Comparison of the prognostic value of MUST, ECOG-PS, mGPS and CT derived body composition analysis in patients with advanced lung cancer. (December 2020) - Abbass, Tanvir; Dolan, Ross D.; MacLeod, Nicholas; Horgan, Paul G.; Laird, Barry J.; McMillan, Donald C.
Summary: Background: Assessment of malnutrition, performance status and systemic inflammation are routine aspects of clinical assessment in patients with advanced cancer. There is increasing evidence that body composition measurements from routine staging CT also have prognostic value. To date the relative prognostic value of Malnutrition Universal Screening Tool (MUST), Eastern Cooperative Oncology Group Performance Status (ECOG-PS), modified Glasgow Prognostic score (mGPS) and CT derived body composition analysis in patients with advanced lung cancer has not been examined. The aim of the present study was to examine this relationship. Methods: Clinicopathological characteristics including MUST, ECOG-PS, mGPS and body composition data were collected pre-radiotherapy from a prospectively maintained database of patients with advanced lung cancer (n = 643). Using the MUST score, patients were classified into low (MUST = 0, n = 189), medium (MUST = 1, n = 341) and high (MUST ≥ 2, n = 113) malnutrition risk and their relationship to systemic inflammatory response (SIR) and body composition with clinical outcomes were examined using univariate and multivariate analyses. Primary outcome of the study was overall survival. Results: Compared with the patients at low nutrition risk (MUST = 0), patients at moderate to high risk (MUST 1–≥2) had poorer ECOG-PS > 1 (p < 0.01), elevated modified frailty index (mFI) (p < 0.001), elevated mGPS (p < 0.001), lower skeletal muscle index (SMI, p < 0.01) but not lower skeletal muscle density (SMD, p = 0.115). MUST was an important prognostic marker of 12 months overall survival (p = 0.001). On multivariate analysis, higher MUST (HR 1.16, 95% CI 1.03–1.31, p < 0.05), ECOG-PS > 1 (HR 1.23, 95% CI 1.10–1.39, p < 0.001), elevated mGPS (HR 1.20, 95% CI 1.09–1.33, p < 0.001) were independently associated with overall survival. Conclusion: A large proportion of patients (71%) with advanced lung cancer were at moderate to high nutrition risk. Higher malnutrition risk and elevated inflammatory status were independently associated with poor overall survival. MUST, ECOG-PS and mGPS all had independent prognostic value and may form an important prognostic framework in treatment decision making and resource utilization